Determining net single premium for credit life insurance at civil servants cooperative of State Polytechnic of Bali - Sukraini, Tri Tanami; Vini Elfarosa, Ketut (Proceedings; Vol 1 No 1 (2017): Proceeding IJCST 2017, 2018)
Credit life insurance is a kind of term life insurance, which is the debtor's life is insured and the amount of coverage is limited by the value of the loan. This study aims to calculate the value of single net premiums, where things that taken into account are mortality and interest rates. This research was conducted in the unit of savings and loan of Civil Servant Cooperative at State Polytechnic of Bali (KPN PNB). In the calculation of premiums, there are two systems of payment of benefits, namely the system of instantaneous payment at death (continuous) and at the end of the year of death (discrete). This study links the two systems by analyzing the value of Actuarial Present Value (APV). The rate of interest is referring to the Bank of Indonesia rate of 6.5%. The results of the calculation analysis showed, by sex, the value of female APV is lower than men this is due to the probability of death of men greater than women. The higher the age, the increased chance of death. Women are considered to have better insurance risk than men. The age factor and the loan term affect the value of a single net premium.